Organizational approach to Total Quality Management: a case study - Islam, Rafikul; Mustafa, Mohamad Reeduan (University of Malaya, 2008)

(untitled)
Malaysian Administrative Modernization and Management Planning Unit (MAMPU) has outlined Total Quality Management (TQM) by means of seven core principles: (1) top management commitment, (2) strategic quality planning, (3) customer focus, (4) training and recognition, (5) enhancing teamwork, (6) performance measurement, and (7) quality assurance. Malaysian organizations are encouraged to apply these core principles in order to attain competitive advantage in the marketplace. The present study is conducted to survey the level of awareness and implementation of those principles in a Malaysian organization. The data have been collected through a questionnaire survey and interview. Seventy two of the total of 125 employees of the organization participated in the survey. Details of the findings are discussed and implications are highlighted.